Search for physics beyond the standard model in events with two leptons, jets, and missing transverse momentum in pp collisions at √s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; Hoermann, N.; et al. (SPRINGER, 2015)
A search is presented for physics beyond the standard model in final states with two opposite-sign same-flavor leptons, jets, and missing transverse momentum. The data sample corresponds to an integrated luminosity of 19.4 fb(-1) of proton-proton collisions at root s = 8TeV collected with the CMS detector at the CERN LHC in 2012. The analysis focuses on searches for a kinematic edge in the invariant mass distribution of the opposite-sign same-flavor lepton pair and for final states with an on-shell Z boson. The observations are consistent with expectations from standard model processes and are interpreted in terms of upper limits on the production of supersymmetric particles.
Keywords: Supersymmetry; Hadron-Hadron Scattering; PARTON DISTRIBUTIONS; SQUARK; Physics